BRCA1-Associated Protein 1 and Its Role of Cell Cycle Regulation in Cancer: BRCA1-Associated Protein 1 In Cell Cycle Regulation - Husain, Syarifuddin; Mohamed, Ruzianisra; Abd Halim, Khairul Bariyyah; Mohd Mutalip, Siti Syairah (Journal of Tropical Life Science, 2026)
BRCA1-associated protein 1 (BAP1) plays a critical role in regulating the cell cycle, exhibiting both tumor-suppressive and oncogenic roles. It controls the expression and stability of key cell cycle regulators, including cyclin D1, p27, and Krüppel-like factor 5 (KLF5), ensuring proper progression through the G1–S checkpoint. Dysregulation of these processes due to altered BAP1 activity can promote uncontrolled proliferation and contribute to tumor progression. This review focuses on the dual roles of BAP1 in cell cycle regulation and highlights how its functional impairment creates vulnerabilities that can be therapeutically exploited. Cyclin D1 is discussed as a potential target to mitigate cell cycle dysregulation driven by BAP1. By emphasizing the molecular mechanisms underlying BAP1 influence on transcriptional programs and protein stability, this work provides insights into strategies for managing malignancies associated with altered BAP1 activity. Mechanistic studies indicate that BAP1 exerts tumor-suppressive effects by interacting with Host Cell Factor-1, Breast Cancer Type 1 Susceptibility protein/BRCA1-Associated RING Domain 1, and KLF5 to maintain proper cell cycle progression. Conversely, BAP1 can exert oncogenic roles in certain cancers by stabilizing KLF5, enhancing cyclin D1 expression, and suppressing p27, thereby promoting proliferation through the Phosphoinositide 3-Kinase/Protein Kinase B/Mechanistic Target of Rapamycin and E2F/Retinoblastoma pathways. These findings underscore cyclin D1 as a convergent node of BAP1-mediated regulation, highlighting its potential as a therapeutic target to restore cell cycle control in malignancies driven by BAP1 dysfunction.